From National Exile to Institutional Blindness: Mirela, a Congolese child - Maicon Salvino Nunes de Almeida; Mônica Pereira dos Santos; Carine Mendes da Silva (Universidade Federal do Rio Grande do Sul, 2021)
The present paper aims to discuss a certain institutional blindness observed in a state school of the state of Rio de Janeiro while investigating the case of a Congolese refugee in Brazil. We carried out a qualitative research, of the case-study type (Yin, 2010) in which we observed a refugee student in the school where she was enrolled and interviews with educators e other social actors. Our analysis is based on the Omnilectical Perspective (Santos, 2013). The results showed that the school might have developed what we called an institutional blindness when it comes to the inclusion of refugee students despite the good intentions of the educational professionals.